2017
DOI: 10.1016/j.freeradbiomed.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Administration of 5-methoxyindole-2-carboxylic acid that potentially targets mitochondrial dihydrolipoamide dehydrogenase confers cerebral preconditioning against ischemic stroke injury

Abstract: The objective of this study was to investigate a possible role of mitochondrial dihydrolipoamide dehydrogenase (DLDH) as a chemical preconditioning target for neuroprotection against ischemic injury. We used 5-methoxyindole-2-carboxylic acid (MICA), a reportedly reversible DLDH inhibitor, as the preconditioning agent and administered MICA to rats mainly via dietary intake. Upon completion of 4 week’s MICA treatment, rats underwent 1 h transient ischemia and 24 h reperfusion followed by tissue collection. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 98 publications
2
33
0
Order By: Relevance
“…During our studies of mitochondrial dysfunction in stroke injury, we stumbled upon a chemical called 5-methoxyindole-2-carboxylic acid (MICA) ( Figure 1 ), which exhibits a potential role in neuroprotection against stroke injury when applied as either a preconditioning or postconditioning agent. 4 , 5 MICA is often regarded as a biomarker for malignant melanoma, 6 but intriguingly, a quick literature search indicates that MICA is actually also a hypoglycemic agent. 7 , 8 In fact, this chemical, having an indole nucleus core structure that is known to possess antidiabetic properties, 9 , 10 was studied extensively in 1960s and 1970s in terms of its glucose-lowering ability.…”
Section: -Methoxyindole-2-carboxylic Acid As a Hypoglycemic Agentmentioning
confidence: 99%
See 3 more Smart Citations
“…During our studies of mitochondrial dysfunction in stroke injury, we stumbled upon a chemical called 5-methoxyindole-2-carboxylic acid (MICA) ( Figure 1 ), which exhibits a potential role in neuroprotection against stroke injury when applied as either a preconditioning or postconditioning agent. 4 , 5 MICA is often regarded as a biomarker for malignant melanoma, 6 but intriguingly, a quick literature search indicates that MICA is actually also a hypoglycemic agent. 7 , 8 In fact, this chemical, having an indole nucleus core structure that is known to possess antidiabetic properties, 9 , 10 was studied extensively in 1960s and 1970s in terms of its glucose-lowering ability.…”
Section: -Methoxyindole-2-carboxylic Acid As a Hypoglycemic Agentmentioning
confidence: 99%
“…It should be noted that MICA inhibition of the conversion of pyruvate to acetyl-CoA occurs not only just in the liver but also in many other tissues such as adipose, testis, brain, and kidney. 5 , 12 , 19 , 20 The establishment that MICA inhibits DLDH is based on the evidence that the cofactor lipoic acid instead of other cofactors such as thiamine and thiamine pyrophosphate can reverse MICA inhibition of DLDH. 14 …”
Section: -Methoxyindole-2-carboxylic Acid As a Hypoglycemic Agentmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated extracellular LDH is a biomarker of oxidative stress and disrupted cell sincerity throughout the lipid peroxidation and oxidative stress. Tao 74 reported that increased level production of LDH cause Aβ accumulation is probably involved in the pathophysiology of AD. Administration of Gb and Ph to AD groups caused a pronounced reduction in the elevated activity of LDH as compared with Alzheimer's group.…”
Section: Table 2: the Effect Of The Aqueous Extract Of Gb Or / And Phmentioning
confidence: 99%